1987
DOI: 10.5006/1.3583151
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mn Additions on the Corrosion Behavior of Mould-Cast Magnesium ASTM AZ91

Abstract: One of the major causes of magnesium corrosion is the presence of iron as an impurity in commercial alloys. Alloying the material with manganese may reduce the corrosion rate to acceptable levels. The corrosion rate of a Mg-9% AI-1 % Zn alloy, containing varying amounts of Mn and Fe, correlates with the Fe:Mn ratio in the alloy and in the aluminum-base intermetallics. The ratio is suggested to be the basic parameter determining the corrosion rate for a given thermomechanical history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(60 citation statements)
references
References 0 publications
7
53
0
Order By: Relevance
“…Poor corrosion resistance on the un-coated 3N-Mg and the uncoated AZ31 alloy are considered to be due to occurrence of filiform corrosion. On the un-coated AZ91E alloy, filiform corrosion did not occur, but internal regions surrounded by grain boundary phase are observed to be predominantly corroded, which agree with results reported by Song et al 10) and Lunder et al 15) 100 µm Homogeneous microstructures with high purity and without second phases and segregations provide superior corrosion resistance for the coated specimens.…”
Section: High-purity Magnesium Coating On Magnesium Alloys By Vapor Dsupporting
confidence: 82%
“…Poor corrosion resistance on the un-coated 3N-Mg and the uncoated AZ31 alloy are considered to be due to occurrence of filiform corrosion. On the un-coated AZ91E alloy, filiform corrosion did not occur, but internal regions surrounded by grain boundary phase are observed to be predominantly corroded, which agree with results reported by Song et al 10) and Lunder et al 15) 100 µm Homogeneous microstructures with high purity and without second phases and segregations provide superior corrosion resistance for the coated specimens.…”
Section: High-purity Magnesium Coating On Magnesium Alloys By Vapor Dsupporting
confidence: 82%
“…A weight ratio Fe/Mn of 0.032 is widely defined to be the threshold above which the corrosion rate highly increases [77,130,131]. Mercer and Hillis [132] found that the Fe tolerance levels for AE42 and AM60 alloys are different, but comparable when considering the Fe/Mn ratio.…”
Section: Tolerance Levelmentioning
confidence: 99%
“…Adding Mn as alloying element to Mg-Al improves corrosion resistance by increasing the Fe tolerance level [77,130,131]. A weight ratio Fe/Mn of 0.032 is widely defined to be the threshold above which the corrosion rate highly increases [77,130,131].…”
Section: Tolerance Levelmentioning
confidence: 99%
“…Other studies [34,35] have confirmed that the α-phase is less noble than β-Mg 17 Al 12 . The higher corrosion resistance of the β-phase has been attributed to the formation of a passive film on its surface [15,18]. A similar occurrence was observed for η-Al 8 Mn 5 particles in 1 M NaOH; this was followed by the formation of pits around these particles [36].…”
Section: Introductionmentioning
confidence: 54%